The costs of civil justice and who pays? - Higgins, A (Oxford University Press, 2017)
This article examines current debates about delivering access to justice in a shrinking state, specifically the Supreme Court’s claim in Coventry v Lawrence (No 3) [2015] UKSC 50 that it is impossible to deliver access to justice for all litigants without widely available legal aid, and broader claims that the state is failing in its duty to provide access to justice for all. It argues that the level of public subsidy and the balance between public and private funding for civil justice systems is a question of distributive justice. A critical review of private funding models demonstrates that some have been denied access to justice. However, requiring litigants to pay for their own access to justice, or to even subsidise access for other litigants, is defensible in principle and practice. Private funding models based on cross-subsidisation between users could substantially reduce the access to justice ‘gap’ experienced by many, provided they meet certain criteria.